Reproductive Features of Patients with Secondary Infertility - Shamim Akhtar, Rizwana Nasreen, Humaira Bibi, Ayesha Azhar Khan, Asma Amin Baig, Najia Riffat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Childlessness is a very pain full situation. It affects both partners but more to females. Burden of secondary infertility is more than primary infertility but it is not captured properly. Secondary infertility also has significant psychological, personal and marital sufferings. Social pressures add the anxiety if only daughters are born. Aim: To find out the reproductive characteristic features of patients presenting with secondary infertility. Place and duration: This retrospective cross sectional study was conducted in Health Care Center Hospital (Pvt) Ltd from July 2021 to September 2022. Method: All patients with secondary infertility of more than one year were included who had previous one or more spontaneous conceptions irrespective of pregnancy outcome. Patients who had no record of previous pregnancies and those who conceived after infertility treatment were excluded. Clinical history was checked from patient’s files and delivery registers. Data was entered in preformed Performa and analyzed by SPSS Version 20. Frequencies were calculated by percentages. Results: Total 115 patients with secondary infertility were included. Sixty one patients had one or more parity, 54 patients had miscarriages. Fifty eight patients had alive babies and 3 babies died. Among 58 live babies 40 patients had only females, 12 had only male and 6 had both male and female children. Among 61 para women, forty three patients had vaginal delivery, 33 normal vaginal and 10 were instrumental deliveries. Cesarean Section was done in 18 patients, 13 were emergency and 05 elective C/S. Practical implication This study will help to understand the burden and factors contributing to secondary infertility. This will guide to manage those factors so that to lesson the secondary infertility. Conclusion: Secondary infertility is an important issue in gynaecological clinics. These patients usually have some identifiable risk factors. Their case should be reviewed carefully to find out the risk factors for proper management. Keywords: Infertility, tubal factor, STDs, miscarriage, Cesarean section,